The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1073/pnas.1315927110
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphonate-degrading PhnZ reveals an emerging family of HD domain mixed-valent diiron oxygenases

Abstract: The founding members of the HD-domain protein superfamily are phosphohydrolases, and newly discovered members are generally annotated as such. However, myo-inositol oxygenase (MIOX) exemplifies a second, very different function that has evolved within the common scaffold of this superfamily. A recently discovered HD protein, PhnZ, catalyzes conversion of 2-amino-1-hydroxyethylphosphonate to glycine and phosphate, culminating a bacterial pathway for the utilization of environmentally abundant 2-aminoethylphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
106
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(128 citation statements)
references
References 45 publications
(60 reference statements)
16
106
0
Order By: Relevance
“…During review of this manuscript Wörsdörfer et al reported elegant Mössbauer and EPR spectroscopic data confirming that PhnZ uses a mixed-valence di-iron active site for catalysis (30). They also reported a low-resolution X-ray crystal structure of PhnZ bound to (R)-2 together with a citrate bound structure.…”
Section: Discussionmentioning
confidence: 92%
“…During review of this manuscript Wörsdörfer et al reported elegant Mössbauer and EPR spectroscopic data confirming that PhnZ uses a mixed-valence di-iron active site for catalysis (30). They also reported a low-resolution X-ray crystal structure of PhnZ bound to (R)-2 together with a citrate bound structure.…”
Section: Discussionmentioning
confidence: 92%
“…4A). The two metal centers are separated by 5.3-and 5.2-Å for the OxsA OXT-PP and OxsA OXT-PPP structures, respectively, which is different from other HD domain dinuclear sites, which are separated by 3.4-3.8 Å[PDB ID codes 3TM8 (11), 2IBN (29), 3CCG 2O08, 2OGI, 2PQ7, and 4N6W (18)] and bridged by the HD doublet Asp residue (Fig. 4 E-G).…”
Section: +mentioning
confidence: 99%
“…This difference could be due in part to the fact that the commercially available deoxyribonucleotide compounds are less pure (98-100%, ≥95%, The Fe ions in PhnZ are 3.7 Å apart, bridged by a μ-oxo moiety and a citrate molecule from the crystallization buffer that binds in place of substrate (18). The second Fe site has three protein ligands (18). In A-C, the proposed nucleophilic water is indicated by an asterisk (*).…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations